The Effect of Social Based-Trends Instruction to Students’ Conceptual Understanding in Mathematics - Ezekiel Orozco Pelayo (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The study aimed to compare the effects of social trends-based instruction to conventional method of teaching on students’ conceptual understanding in mathematics. Methodology: The study employed a quasi-experimental research design using test questionnaire which was formulated by the researcher based on the National Council for Teachers in Mathematics (NCTM) principles and standards for teaching mathematics. Data were collected from two groups of First Year BS Hospitatily Management college students, analyzed using Statistical Package for Social Sciences and involved ethics review and informed consent. Main Findings: The study revealed that both social trends-based instruction and traditional instruction methods led to improvements in students' conceptual understanding in mathematics. However, the social trends-based instruction group demonstrated higher scores on students’ learning of the topic. Findings also revealed through the Analysis of Covariance that the type of instruction used in both groups had a significant impact on students’ conceptual understanding. Novelty/Originality of this study: To the best of the researcher's knowledge, no existing study has integrated social trends into mathematics teaching to the extent explored in this research. This study uniquely integrates Social Trends-Based Instruction in teaching mathematics to evaluate its influence on students’ conceptual understanding. This study offers a new perspective for mathematics classroom and serves as an instructional model for mathematics educators to enhance mathematical learning of students. The findings of this study are expected to provide valuable insights for educators, policymakers, and curriculum developers seeking to modernize mathematics instruction.